PENGELOLAAN DAN PEMANFAATAN TANAH ULAYAT DALAM MEWUJUDKAN KESEJAHTERAAN MASYARAKAT ADAT DI DESA KOTO TUO KECAMATAN XIII KOTO KAMPAR KABUPATEN KAMPAR - Rizki Pratama; Hayatul Ismi; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Every society needs land in its life, in indigenous society there is name of hak ulayat which is right of a group of indigenous people on a piece of land called ulayat land. talking about ulayat land, customary land rights holder dupimpin by adat stakeholders or tribal penghulu. Article 9 Regional Regulation of Kampar Regency states that the duty of the tribal elders shall be to organize the government, welfare, and security in their tribal areas in the field of customary law. That is, tribal penghulu obliged to realize the welfare and interests of community members in order to avoid disputes. But the fact that the case of ulayat land in the sale and the management and utilization is no longer in accordance with the existing rules. The purpose of writing this thesis, namely: First to know how the management and utilization of ulayat land in the village Koto Tuo District XIII Koto Kampar, Second to find out what obstacles encountered when the management and utilization of ulayat land in the village Koto Tuo District XIII Koto Kampar.This type of research can be classified sociologically, because in this study the authors directly conduct research on the location or place studied in order to provide a complete and clear picture of the problem under study. This research was conducted in Koto Tuo Village, XIII Koto Kampar Sub-district, Kampar District, whereas population and sample are all parties related to the problem studied in this research, data source used primary data, secondary data, and tertiary data, data collection technique in this research with observation, interview, questionnaire, and literature study.From the research results can be concluded two things. First, Ninik mamak is obliged to maintain ulayat land for welfare and mutual interest. Secondly, the unknown extent of ulayat land and the task of ninik mamak is only determined by the traditional language. Author suggestions Firstly, ninik mamak and indigenous peoples should always conduct deliberations before making a decision. Second, it is expected to ninik mamak and adat community to be more cooperative if there are problems to communal land so that the adat society is not harmed and protected.Keywords: Management - Ulayat Land - Community Welfare